Cry wolf : a novel - Rosenfeldt, Hans, 1964- (Hanover Square Press, 2022)
When human remains are found in the stomach of a dead wolf in the remote northern town of Haparanda, Sweden, policewoman Hannah Wester knows that this summer won't be like any other.